Letter (copy) : Evacuation of refugees from Santander - Tewson, Vincent
037-0058-001 HVT/FC/EW/250 Secretary's 23rd August, 1937. Mrs. Mary M. Miller, National Joint Committee for Spanish Relief, 53, Marsham Street, London, S.W.1. Dear Mrs. Miller, Evacuation of Refugees from Santander. I am enclosing a letter from Mr. Wood of Parkston together with a copy of my reply. Perhaps you would drop him a note. Yours sincerely, Assistant Secretary. 2 letters. 292/946/37/58